2017
DOI: 10.5811/cpcem.2017.1.30607
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Reversible Encephalopathy Syndrome Presenting as Stroke Mimic

Abstract: We present the case of a 33-year-old male with end stage renal disease presenting to the emergency department (ED) with headache, dizziness, and unilateral weakness. Initial concern was for ischemic or hemorrhagic stroke. Magnetic resonance imaging confirmed posterior reversible encephalopathy syndrome (PRES). The patient was treated appropriately and made a full neurologic recovery. PRES is an under-recognized diagnosis in the ED. As a stroke mimic, PRES can lead the clinician on an incorrect diagnostic pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…54 Stroke mimic not recognized as PRES leads to incorrect diagnostic pathway with potential for iatrogenic harm through improper administration of thrombolytic therapy. 66 When compared to the high income countries also, poverty and poor clinical settings in LMIC contributes to the diagnostic challenges and may contribute to limited research interest in pediatric PRES with consequent underreporting of PRES [67][68][69] Most of the reports of pediatric PRES have been from developed countries 2,4,[10][11][12][13][14][15][16][17][18][19][20][21] and a few from Africa. Nandi and colleagues 70 in South Africa were able to diagnose PRES in 4 children with novel aetiological associations: hypoxia following accidental strangulation, near-drowning episode, a child with thalassaemia receiving routine blood transfusions, and a fourth child who had PRES while recovering from toxic epidermal necrolysis syndrome (TENS).…”
Section: Challenges Of Pediatric Pres Diagnosis In Nigeria and Other mentioning
confidence: 99%
See 2 more Smart Citations
“…54 Stroke mimic not recognized as PRES leads to incorrect diagnostic pathway with potential for iatrogenic harm through improper administration of thrombolytic therapy. 66 When compared to the high income countries also, poverty and poor clinical settings in LMIC contributes to the diagnostic challenges and may contribute to limited research interest in pediatric PRES with consequent underreporting of PRES [67][68][69] Most of the reports of pediatric PRES have been from developed countries 2,4,[10][11][12][13][14][15][16][17][18][19][20][21] and a few from Africa. Nandi and colleagues 70 in South Africa were able to diagnose PRES in 4 children with novel aetiological associations: hypoxia following accidental strangulation, near-drowning episode, a child with thalassaemia receiving routine blood transfusions, and a fourth child who had PRES while recovering from toxic epidermal necrolysis syndrome (TENS).…”
Section: Challenges Of Pediatric Pres Diagnosis In Nigeria and Other mentioning
confidence: 99%
“…77 and the utility of more available CT are not highlighted; and because the availability and utilization of MRI units across sub-Saharan Africa countries still remain poor due to enormous acquisition costs, lack of infrastructure and the expertise required for maintaining and running the systems. 66 The diagnosis of PRES may continue to be elusive, until more awareness is created. In addition, the high cost of these imaging studies to the patient paying out-of-pocket, may be prohibitive in developing countries where socioeconomic factors contribute significantly to child neglect 78 and add to the limitations to pediatric PRES diagnosis with associated data loss about pediatric PRES.…”
Section: Challenges Of Pediatric Pres Diagnosis In Nigeria and Other mentioning
confidence: 99%
See 1 more Smart Citation
“…One study demonstrated 58% prevalence of headache in preeclampsia/eclampsia patients with PRES. [ 8 ] Headache attributed to arterial hypertension is yet another syndrome associated with PRES and presents as severe in onset in conjunction with notably high blood pressures [ 9 ]. Prior reports have described headache in patients with PRES receiving associated medications; however, these patients are usually hypertensive at time of diagnosis [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prognosis is generally favorable and the majority of patients make a full recovery, though some diagnostic criteria require clinical and radiographic resolution [ 18 ••] which does not include the entire spectrum of the disease. When reversibility is not mandated, complete recovery is reported in 75–90% of cases, and most patients will recover within a week, though in some patients, recovery occurs over a longer interval and neurological sequelae have been reported in 10–20% of patients [ 9 ]. PRES can also be quite severe, and mortality has been reported in 3–6% of cases [ 67 ].…”
Section: Introductionmentioning
confidence: 99%